CASE 10: Lost in Translation: Developing Strategies for Indigenous People who have Cancer, Limited English Proficiency, and Limited Health Literacy - Martin, Hillary; Papadakos, Janet; Terry, Amanda (Scholarship@Western, 2021)
Studies have documented that people who have limited health literacy and limited English proficiency often have challenges with all aspects of health care, including difficulties accessing health care, understanding medical information, making treatment decisions, taking prescriptions properly, and communicating with health care workers. People who have limited health literacy often have an overall negative outlook about health care, and they are less likely to seek help from health care providers or health programs, which can negatively affect their overall long-term health and lead to poorer health outcomes than those with high health literacy. The main goals of this case are for the reader to understand limited English proficiency and health literacy in the context of health care for Indigenous populations, and to define and apply strategies to effectively communicate with these populations in a health care setting. This case provides the reader with an array of information regarding Indigenous health issues and perspectives. It gives the reader the opportunity to assess a health care problem and identify the social and cultural determinants of health within it. Through the use of concept mapping, the reader will be pushed to explore the relationships between limited English proficiency, health literacy, and Indigenous knowledge and beliefs in a healthcare setting. It will challenge the reader to think critically about the situation and propose strategic interventions to break down communication barriers.